Killing Two Birds With One Stone: Effective Control of Both Non-Small Cell Lung Cancer and Progressive Multifocal Leukoencephalopathy With Atezolizumab, A Case Report - Lambert, Nicolas; El Moussaoui, Majdouline; Ritacco, Caroline; Moïse, Martin; Paulus, Astrid; Delvenne, Philippe; Baron, Frédéric; Sadzot, Bernard; Maquet, Pierre (Frontiers in Immunology, 2022)
Treating patients with cancer complicated by severe opportunistic infections is particularly challenging since classical cancer treatments, such as chemotherapy, often induce profound immune suppression and, as a result, may favor infection progression. Little is known about the potential place of immune checkpoint inhibitors in these complex situations. Here, we report a 66-year-old man who was concomitantly diagnosed with non-small cell lung cancer and progressive multifocal leukoencephalopathy. The patient was treated with anti-PD-L1 antibody atezolizumab, which allowed effective control of both lung cancer and progressive multifocal leukoencephalopathy, as demonstrated by the patient’s remarkable neurologic clinical improvement, JC viral load reduction in his cerebrospinal fluid, regression of the brain lesions visualized through MRI and the strict radiological stability of his cancer. In parallel, treatment with atezolizumab was associated with biological evidence of T-cell reinvigoration. Hence, our data suggest that immune checkpoint inhibitors may constitute a treatment option for patients with cancer complicated by severe opportunistic infections.